Saúde 360: aplicação dos princípios da web semântica para inter-relacionar informação no domínio da saúde - Teixeira, Fabio Oliveira [UNIFESP] (2016)
The growing of the information available on the web, diversifying and democratizing the content sources, motivated the creation of the semantic web, which made it possible to structure information available on the world wide web through the creation of standards, query languages and ontologies. Objective: Construction of an environment governed by the semantic web principles for representation, interrelationships and query the data professionals and healthcare establishments of the Cadastro Nacional de Estabelecimentos de Saúde (CNES) and the Lattes Platform. Method: Development of automated processes for data retrieval from platforms that are originally responsible for its publication. An exploratory process for the selection of 14 relevant ontologies in semantic web universe for the representation of data collected from platforms and subsequent storage in a triple server was realized. A heuristic for identifying the co-occurrence between individuals in the CNES and Lattes was created, promoting the interrelationship between platforms. A tool able to query the data mapped through ontologies and stored in the triple server was evaluated. Result: We created and made available to the scientific community the semantic representations of the data present in Lattes and CNES platforms, containing approximately representation of 2 million individuals. Queries governed by semantic web principles were built and proved the enormous potential for retrieval, interrelatedness and enrichment of data organized by the built environment and object of this thesis. Conclusion: The proposed environment empower the interrelationship and enrichment of data from the Lattes Platform and CNES, between and with other databases available on the Web of Data. The use of ontologies suggested by the scientific community ensured the semantic assumptions of interrelationships in the built environment.